Fusion of Creativity and Precision: Guidelines for Effective Leadership - Irani Tarigan, Miska (Escalate : Economics and Business Journal, 2024)
This article examines the intricate interplay of key organizational variables within PT Dharma Niaga Medan, including leadership effectiveness, market conditions, team creativity, and execution fidelity. Utilizing direct and indirect effects analyses with robust statistical methods, the research uncovers significant relationships among these variables. The results emphasize the critical impact of team creativity and execution fidelity on leadership effectiveness, both directly and indirectly through their influence on market conditions. The findings underscore the interconnected nature of these organizational elements, highlighting the importance of cultivating a creative team environment and precise execution for optimal leadership efficacy. Additionally, the study underscores the relevance of market conditions in shaping effective leadership strategies. The insights derived from this research offer valuable guidance for organizational leaders in PT Dharma Niaga Medan, providing pathways for enhancing team dynamics, execution strategies, and adaptive responses to market dynamics for a resilient and effective organizational framework.